The History of Jama‘ah Tabligh in Southeast Asia: The Role of Islamic Sufism in Islamic Revival - Kamaruzzaman Bustamam-Ahmad (Al-Jami'ah: Journal of Islamic Studies, 2008)
The article examines the history of Jama‘ah Tabligh in Southeast Asia, especially in Kuala Lumpur and Aceh. The author traces the historical background of this religious movement with particular reference to the birth place of Jama‘ah Tabligh , India. The author investigates the major role of Indian in disseminating Islam in Southeast Asia, especially in Malaysia and Indonesia. Many scholars believe that Islam came to Southeast Asia from India (Gujarat), and this is the reason why many Islamic traditions in this region were influenced by Indian culture. However, to analyze Islamic movement in Southeast Asia one should take into consideration the Middle East context in which various Islamic movements flourished. Unlike many scholars who believe that the spirit of revivalism or Islamic modernism in Southeast Asia was more influenced by Islam in the Middle East than Indian, the author argues that the influence of Indian Muslim in Southeast Asia cannot be neglected, particularly in the case of Jama‘ah Tabligh.